A Bibliometric Analysis of Economic Inclusiveness in Developing Countries - Loso Judijanto; Heri Setiyawan; Nur Hasan Kurniawan (West Science Interdisciplinary Studies, 2024)
This study presents a bibliometric analysis aimed at mapping the academic landscape of economic inclusiveness in developing countries from 2000 to 2024. Through a comprehensive review of the literature, this analysis identifies core themes including governance, sustainability, financial inclusion, and education, emphasizing their roles in fostering equitable economic growth. Using data sourced from Scopus, the study employs VOSviewer software for visualization of co-authorship and co-citation networks, revealing prominent authors, pivotal publications, and thematic clusters. The results highlight an interdisciplinary approach in the research with significant contributions from various global regions, showcasing the complexity of implementing economic inclusiveness across different socio-economic and environmental contexts. The findings underline the necessity of integrating sustainable practices and robust governance to ensure inclusiveness and suggest directions for future research to fill the existing gaps in empirical data and cultural considerations.